Shifting sociological paradigms and working class criminality - Chandraratna, D. (NARESA:Colombo, 1983)
An attempt is made to explain working class criminality through the shifting approaches of different sociological paradigms.It then tries to link up the political response that parellels each sociological paradigm.Overall,this essay gives an account of the intimate connection that exists between the ideas we have and the sort of life that we lead and it is in this light the criminality of the working class is explained.
Keywords: Sociological problems; Victims; Law